THE RELATIONSHIP OF FAMILY SUPPORT WITH QUALITY OF LIFE AMONG PATIENTS WITH CHRONIC KIDNEY DISEASE IN RUNNING HEMODIALIZATION THERAPY AT PMI HOSPITAL BOGOR: HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA DI RS PMI BOGOR - Fajar Adhie Sulistyo (Wijaya Husada, 2018)
Background : Chronic kidney disease is a pathophysiological process with diverse etiology, resulting in a progressive decline in renal function, and the patients generally end up with kidney failure. Family support is a support given by families who have blood relations in favor of the health of patients with kidney failure. Quality of life is an individual perception of patients with kidney failure toward his position in life. The aim of this study was to determine the relationship of family support with the quality of life of patients with chronic renal failure undergoing hemodialysis therapy in PMI hospital Bogor. The method of this research uses uses descriptively analytic type with cross sectional approach. The sample of this researchconsists of 129 respondents. The sampling was taken by accidental sampling technique. The instrument in this study were questionnaires family support and quality of life. The data were analyzed by using univariate and bivariate (using the chi-square test with α = 0.05). Result : Based on the research results through 88 respondents that (68.2%) whose family support is good, then 86 respondents (93%) have a good quality of life, and 2 respondents (5%) have less quality of life. From 8 respondents (6.2%) whose family support is less, 1 respondent (2%) have a good quality of life, and 7 respondents (19%) have a less quality of life. Based on statistical test p = 0.000, it can be concluded that there is significant correlation between both variables. Clonclusion : It is concluded that there is a relationship between family support and the quality of life among patients with chronic renal failure undergoing hemodialysis therapy in PMI hospital Bogor. Through this research, it is expected to be used as a source reference of information for nurses in hemodialysis room.